EFFECT OF SALINITY ON THE PHYSIOLOGICAL BEHAVIOR OF THE OLIVE TREE (VARIETY SIGOISE - Boualem, S; Boutaleb, F; Ababou, A; Gacem, F (university of el oued/جامعة الوادي, 2019)
Salinity is a major problem directly affecting the ecological balance and the development of agriculture in the Mediterranean basin, particularly North Africa. This phenomenon is considered as the most important abiotic factor limiting crops growth and productivity, degrading and polluting soils in arid and semi-arid. In order to study the influence of salinity, on the physiological parameters and to assess the potential of adaptation of the olive tree in a saline environment, three parcels containing the Sigoise variety and subject to different degrees of salinity were selected: Parcel 1 (non-saline); Parcel 2 (saline); Parcel 3 (very saline). Under a saline constraint, the results showed two contrasting tendencies, an intense increase in the content of proline, sodium (Na+) and chlorophyll (b), while water content, potassium and chlorophyll (a) decreased strongly with increasing salinity.
Article
Keywords: Salinity; olive tree; salt stress; proline; chlorophyll.